ANALYSIS OF THE STRATEGY FOR DISTRIBUTING ZIS FUNDS THROUGH THE TEACHER CARE PROGRAM AT LAZISMU, SURAKARTA CITY - Ayub Makrub Islamudin; Irsan Irsan (Universitas Nurul Jadid, 2025)
Poverty is a major problem in Indonesia that continues to be faced to this day. Lazismu Surakarta City comes with a program that provides solutions in the midst of the void of things that escape the government's attention. This study aims to analyze the strategy of distributing ZIS funds through the teacher care program at Lazismu Surakarta. The method used in this research is a qualitative method, the data source of this research uses primary and secondary data, primary data collected by interview, observation and documentation directly at the Surakarta lazismu office while secondary data is obtained from various kinds of journal literature, lazismu official web, articles and others. The results of this study indicate that the strategy of channeling ZIS funds carried out by Lazismu Surakarta is among others: cooperating with the Education Council of the Regional Leadership of Aisyiyah Surakarta to survey, each teacher is given an account number on behalf of the teacher, using BPRS HIK Surakarta bank as a distribution, gathering all selected teachers at the beginning of the year and certain moments. Sharia review of the strategy of distributing ZIS funds through the teacher care program in the lazismu of Surakarta city is generally in accordance with the guidance of the Qur'an and As sunnah, teachers can receive subsidies from zakat funds as part of the fiisabilillah group, because their role in preparing cadres of people is a form of jihad in the way of Allah and efforts to uphold the sentence of Allah, the use of banks as wasilah in transferring zakat is permissible because there is no element of forbidden, lazismu feedback to the BPRS HIK bank should not be necessary because this can diminish or weaken the sincerity of those who give zakat.